Effectiveness of Fiscal Criminal Law Enforcement in Handling Criminal Acts in the Taxation and Customs Sector - N., Anggiat Ris Hardinata; Vic, Binsar Jon (Green Publisher Indonesia, 2025)
Fiscal criminal law enforcement has a strategic role in protecting the fiscal interests of the state, especially in the taxation and customs sectors which are the main sources of state revenue. This study aims to analyze the effectiveness of fiscal criminal law enforcement in handling criminal acts that are detrimental to state revenue, with a focus on the provisions stipulated in the Law on General Provisions and Tax Procedures (UU KUP), the Law on Harmonization of Tax Regulations (UU HPP), and the Customs Law. The research method used is a normative legal approach with an analysis of relevant laws and court decisions. The results indicate that although there have been quite comprehensive regulations, there are still challenges in coordination between law enforcement agencies, gaps between administrative and criminal sanctions, and obstacles to proof. Therefore, it is necessary to strengthen the law enforcement mechanism and harmonize regulations to improve the effectiveness of handling fiscal crimes as a whole.